Gerakan penegakan syariah: studi gerakan sosial Hizbut Tahrir Indonesia di DIY - Muhsin, Illya (Sekolah Tinggi Agama Islam Negeri Salatiga, 2012)
After the new order (ORBA) has collapsed, HTI is the most solid and has the widest network among the other new Islamic movements that always struggle to implement the Sharia. Furthermore, HTI is the most radical movement because HTI does not only have aims to implement the Sharia but to build Islamic caliphate as well. How the Sharia concept in caliphate frame and the HTI effort in realizing the aims is the focus of this qualitative research. To answer this question, the researcher interviews some HTI activists and attends in some HTI activities in Yogyakarta. According to HTI, the Sharia encompasses every life aspect; such as worship, ethic, food, drink, dress or muâamalah (government, economy, education, justness. Etc). The Sharia can only be applied perfectly (kaffah) in the Islamic caliphate system. The efforts of HTI in implementing the Sharia in the system of caliphate country are explained by using the Doug Macadamâs theories of social movement; those are 1) political opportunities 2) mobilizing structures; either internal, by tathqif, or external, by tathqif jamaâi and talab al-nusrah, 3) framing process by siraâ al-fikri, kifah siyasi and tabanni masalih al-âummah. Refering to the social movement, HTI is a revolutionary movement which aims to replace the old social order at all by a new system. This movement tries to save and free the ummah from the broken and kufr system along with social critics to some social troubles which create crisis in life. Therefore, HTI will grow widely in social order which is full of poverty, injustice, corruption and all arbitrariness. Otherwise, HTI will be difficult to be big movement in the prosperous and just countries.